MODERASI BERAGAMA DAN RELEVANSINYA UNTUK PENDIDIKAN DI SEKOLAH KATOLIK - Tomas Lastari Hatmoko; Yovita Kurnia Mariani (Bahasa Indonesia, 2022)
The diversity of religions, beliefs, ethnicities, languages, and cultures shows that Indonesia is so rich and beautiful. However, waves of radicalism or religious fundamentalism that leads to conflict and violence have continued to spread over the years in the world, including Indonesia. Radicalism that breeds intolerance is a threat to the integrity of the nation. Since 2019 the government through the minister of religion has paid attention to building a religious moderation program in Indonesia. Religious moderation is a government program that is always actual for the Indonesian people. The Indonesian Catholic Church takes part in spreading the values ​​of religious moderation especially through education. The purpose of this study is to explore the values of the diversity in Indonesia, religious moderation, and application in the Catholic Schools. In developing this paper, the author uses the literature study method. The Catholic religious education in schools is a way to educate children to believe, without going to extremes